Can Grid Governance Fix the Party-state's Broken Windows? A Study of Stability Maintenance in Grassroots China. (7th September 2022) - Xu, Jianhua; He, Siying
Abstract: Grid governance has been developed by the Chinese party-state to collect intelligence at the grassroots level for the early pre-emption of what it defines as social instability. Using data collected from four months' participant observation and extensive interviews with personnel who work in the grid governance system in what we call W Street, a location in a second-tier city in southern China, this paper examines how China's grid governance is used for stability maintenance and how in practice the system has become alienated from its original purpose of social control. We find that grid governance is achieved mainly through three mechanisms: intelligence gathering, case coordination and real-time reporting for stability maintenance. We further reveal that while grid governance provides an important infrastructural power for intelligence gathering, the realization of this power could be hindered by contradictory logics among different levels of government. This research not only provides empirical data on how China's grid governance works in practice but also calls for a rethinking of the capacity of China's stability maintenance regime.